Volume 4A: Dynamics, Vibration, and Control 2014
DOI: 10.1115/imece2014-37116
|View full text |Cite
|
Sign up to set email alerts
|

Feature Extraction Algorithm Fusion for SONAR Sensor Data Based Environment Mapping

Abstract: Mobile platforms that make use of concurrent localization and mapping algorithms have industrial applications for autonomous inspection and maintenance, such as the inspection of flaws and defects in oil pipelines and storage tanks. An important component of these algorithms is feature extraction, which involves detection of significant features that represent the environment. For example, points and lines can be used to represent features such as corners, edges, and walls. Feature extraction algorithms make u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This manuscript follows previous studies reported by the authors [13], [14]. The authors have organized the material into five sections.…”
Section: Indexmentioning
confidence: 86%
See 1 more Smart Citation
“…This manuscript follows previous studies reported by the authors [13], [14]. The authors have organized the material into five sections.…”
Section: Indexmentioning
confidence: 86%
“…(1) input raw SONAR data to the fusion algorithm; (2) apply limit constraints to the SONAR data and accept only SONAR [14]. range data between 50 cm and 200 cm.…”
Section: Proposed Algorithm Combinationmentioning
confidence: 99%